2022
DOI: 10.1111/rec.13778
|View full text |Cite
|
Sign up to set email alerts
|

Understanding anthropogenic impacts on zoogeochemistry is essential for ecological restoration

Abstract: Ecological restoration is critical for climate and biodiversity resilience over the coming century. Today, there is strong evidence that wildlife can significantly influence the distribution and stoichiometry of elements across landscapes, with subsequent impacts on the composition and functioning of ecosystems. Consequently, any anthropogenic activity that modifies this important aspect of zoogeochemistry, such as changes to animal community composition, diet, or movement patterns, may support or hinder resto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 100 publications
0
12
0
Order By: Relevance
“…While understanding the ecosystem‐wide casual feedback effects propagated by parturition (and resulting landscape heterogeneity) is beyond the scope of this paper, our study highlights one newly discovered piece of an infinite feedback loop between animals and ecosystems (Veldhuis et al, 2018). Complementary work using modelling grounded in field data would enhance a broader understanding of the landscape and population consequences of the kinds of ecosystem impacts we examined in our study (Abraham et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…While understanding the ecosystem‐wide casual feedback effects propagated by parturition (and resulting landscape heterogeneity) is beyond the scope of this paper, our study highlights one newly discovered piece of an infinite feedback loop between animals and ecosystems (Veldhuis et al, 2018). Complementary work using modelling grounded in field data would enhance a broader understanding of the landscape and population consequences of the kinds of ecosystem impacts we examined in our study (Abraham et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…4), but may lead to degradative ecosystem impacts such as soil compaction, overgrazing, or disease transmission (He et al 2022, Abraham et al 2022a). In addition, the use of natural and artificial licks by large herbivores may substantially alter animal roles in nutrient dispersal (Abraham et al 2022b). Other alterations to Na‐poor environments, such as road salting (Hintz and Relyea 2019, Vignisdottir et al 2019), oil drilling (Moquet et al 2014), gold mining (Akcil 2002, Bury 2004), deforestation (Corbould et al 2010, Veldkamp et al 2020), carcass removal (Abraham et al 2021), saline irrigation (Rengasamy and Olsson 1993), climate change (Mahowald et al 2006), and human urine deposition (Kirchmann and Pettersson 1994) may affect animals and ecosystems in similar or opposite ways by inducing or alleviating Na limitation, and represents an important avenue of future research.…”
Section: Discussionmentioning
confidence: 99%
“…Other topics getting relatively short shrift in restoration include zoogeochemistry-how stoichiometry of animals varies across landscapes (Abraham et al, 2023), the role of restoration in human health through the prevention of zoonotic disease transmission (Prist et al, 2023;Reaser et al, 2021), and how historical events shape the aspirations and limitations of restoration (Case & Hallett, 2021). The difficulty of scaling up restoration while dismantling social inequity was highlighted, with suggestions to reconcile these often-opposing goals (Sigman, 2021).…”
Section: Under App Rec Iated In Restor Ationmentioning
confidence: 99%
“…The importance of mycorrhizal fungi in facilitating the growth and survival of certain plants was emphasized (Aavik et al, 2021; Frewert et al, 2022; Koziol et al, 2022; Rubin & Görres, 2023), but found to be significantly underrepresented in management plants (Markovchick et al, 2023). Other topics getting relatively short shrift in restoration include zoogeochemistry—how stoichiometry of animals varies across landscapes (Abraham et al, 2023), the role of restoration in human health through the prevention of zoonotic disease transmission (Prist et al, 2023; Reaser et al, 2021), and how historical events shape the aspirations and limitations of restoration (Case & Hallett, 2021). The difficulty of scaling up restoration while dismantling social inequity was highlighted, with suggestions to reconcile these often‐opposing goals (Sigman, 2021).…”
Section: Underappreciated In Restorationmentioning
confidence: 99%